2022
DOI: 10.3390/cryst12040504
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Synthesis to Disperse Zeolite NaY in Lead Tree Wood

Abstract: The goal of this work is to synthesize zeolite NaY inside Lead tree wood. The wood is mixed with zeolite seed gel before mixing with feed gel and subsequent hydrothermal treatment. In the first trial, the dried and untreated Lead tree wood is mixed with the gel of zeolite NaY before the hydrothermal process. Only zeolite NaP is produced. Then, sonication is applied to the wood and zeolite gel mixture before the hydrothermal process. The product is mixed with the phase of NaP and NaY. In the next attempt, the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Zeolite can be dispersed to form composites with various substrates (Table 1), including polymers [4], ceramics [5], carbon from various sources [6][7][8][9], cellulose [10][11][12], and wood [13]. Valtchev et al [11] prepared wood-zeolite composites between zeolite A (LTA) and wood substrates with different amounts of lignin and cellulose.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeolite can be dispersed to form composites with various substrates (Table 1), including polymers [4], ceramics [5], carbon from various sources [6][7][8][9], cellulose [10][11][12], and wood [13]. Valtchev et al [11] prepared wood-zeolite composites between zeolite A (LTA) and wood substrates with different amounts of lignin and cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical treatment is, therefore, necessary to eliminate the lignin and enhance the amount of cellulose. Recently, Krukkratoke et al [13] reported the synthesis of zeolite NaY (FAU) in lead tree wood through a hydrothermal method. Zeolite NaY was the major phase in the acid-refluxed wood, whereas zeolite NaP (GIS) was produced in the non-refluxed wood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation